PECULIARITIES OF A SPECIAL-PURPOSE PROGRAM OF FORMING A SYSTEM OF EFFICIENT SOCIO-ECONOMIC DEVELOPMENT OF THE RUSSIAN FEDERATION ON THE REGIONAL LEVEL - Kruglov, Vladimir; Gerasikova, Elena; Lesina, Tatiana; Shaurina, Olga; Maslennikova, Natalia; Aygumov, Timur (Revista Inclusiones, 2019)
In the article the problems on providing a special-purpose program for the growth of socio-economic parameters of dynamically sustainable systems of the socio-economic level in the economic entities of the Russian Federation have been analyzed. The research has been based on the Pareto rule. Twenty percent of the most characteristic regions in terms of the trend have been distinguished from the entire information monolith for the subsequent analysis. Similarly, approximately one fifth of the main legislative acts recently adopted in this area, both at the federal and local levels, have been singled out. In general, this allows creating a fairly labile and realistic picture of the current matter of fact and identifying the main reasons that lie in the shortcomings of the adopted documents and restrain the development of territories. In order to fix weaknesses, the researchers have offered specific measures on improving the special-purpose program through adaptation mechanisms among the available reserves.